The war continues not only on the front: a broader look at PTSD in the context of the Russian invasion and its impact on Ukrainian citizens - systematic rewiev - Monika Adamczyk; Joanna Mazurek; Hubert Stachowicz; Magdalena Ptasznik; Aleksandra Baran; Weronika Bartos; Magdalena Piotrowska; Ewelina Flegiel; Justyna Lenart; Miłosz Podrażka (Kazimierz Wielki University, 2024)
Russia's aggression against Ukraine is undoubtedly a tragic event that will bring various, often difficult to predict, consequences at many levels of functioning. Certainly, the mental health of war victims faces many challenges. The mental health crisis that occurs during war is a public health problem.28 One of the main disorders that appear in people directly or indirectly related to war is PTSD. It arises as a result of experiencing extremely dangerous, terrifying events that go beyond one's ability to cope and is manifested by symptoms such as: obsessive, persistent re-experiencing of traumatic events, avoidance of factors causing a "return" to traumatic memories, excessive arousal and a sense of constant threats.8, 10 Many factors influence the occurrence of PTSD. It is extremely important to look at the reasons that make it difficult to obtain support. mental health and improving the support system. Ukrainian children and youth deserve special attention here. A developing young society must face particularly great challenges, and it is their mental well-being that guarantees better development of the entire nation. Every effort must be made to ensure that citizens of a country at war receive adequate support. We have many methods of help, from basic emergency support, through a wide range of psychotherapy, to medications in the most severe cases. Additionally, the knowledge of the existence of a phenomenon such as post-traumatic growth may give hope and motivation to act to people in mental crisis struggling with symptoms of PTSD. However, the war continues and there will be more and more victims struggling with post-traumatic stress disorder (PTSD) and other mental health disorders. We cannot determine at this point how much damage this conflict will cause. However, it is worth acting now to prevent and limit the tragic consequences of the situation in which Ukraine finds itself.